Functional-aesthetic treatment of crown fracture in anterior teeth with severe crowding - Diego Henrique da Silva Mendonça; Mario Lúcio da Costa Azevedo; José Carlos Dal Secco Leandrini; Aline Evangelista Souza-Gabriel (Revista Sul-Brasileira de Odontologia, 2013)
Traumatic injuries are usually the result of impacts whose aggressive strength exceeds the resistance found in bone, muscle and tooth tissues. With the advent of the etching technique and considering the improvement of composite resins, simpler and more conservative alternatives are indicated in the aesthetic and functional rehabilitation of fractured anterior teeth. Case report and objective: This study aimed to report the treatment of a 13 year-old patient that fractured his central incisor due to a trauma. After clinical and radiographic examination, an oblique crown fracture with extensive involvement of the incisal angle, without pulp exposure or injury to the biological space of the left maxillary central incisor (tooth #21) was observed. Because the fractured tooth fragment was lost, it was not possible to process a fragment bonding. Thus, it was proposed to treat the tooth through direct technique restoration with composite resin. Conclusion: It can be concluded that the aesthetic and functional rehabilitation with direct composite resin is a viable option for the conservative treatment of fractured anterior teeth.